Air Quality Bioindicator Using the Population of Epiphytic Macrolichens in Bogor City, West Java - . RINDITA; LISDAR IDWAN SUDIRMAN; YONNY KOESMARYONO (HAYATI Journal of Biosciences, 2015)
Studies about lichens and pollution in South-East Asia are restricted because the lichens are poorly known. A research project about air quality bioindicator using epiphytic macrolichens in Bogor City was conducted from March 2012 until July 2013. Purposive sampling method was applied in 3 plots: plot 1 was in the centre of Bogor Botanical Garden (BBG) that far from busy roads, plot 2 was in a part of BBG adjacent to main and busy roads, and plot 3 was along busy roads and near a factory. In each plot, macrolichens were observed in 8 canary trees using 2 mini quadrats (32 x 20 cm2). The population conditions of epiphytic macrolichens were analyzed and to be used as bioindicator of air quality. Seven genera of macrolichens were found: Coccocarpia, Leptogium, Canoparmelia, Parmotrema, Dirinaria, Physcia, and Pyxine. Plot 1 was having Coccocarpia and Leptogium that were not found in other plots and therefore they can be used as sensitive bioindicators, none of Canoparmelia and Pyxine, a few and infrequent Dirinaria but with larger average coverage (AC = 6.15 cm2), and Physcia was found abundantly (sensitive bioindicator). Conversely, plot 2 and 3 were having none of Coccocarpia and Leptogium, few or many Canoparmelia and Pyxine and therefore appeared to be tolerant, many and frequent Dirinaria but with smaller AC (plot 2 = 2.85 cm2, plot 3 = 1.16 cm2), and few or none of Physcia was found. Being found in all plots, Dirinaria showed a clear pattern of increasing thallus number and decreasing AC from plot 1 to plot 3, so it can be used as tolerant bioindicator. Conversely, Parmotrema had unclear pattern of population condition. Similar researches on different trees are necessary to explore more details regarding epiphytic macrolichens population condition.